2019
DOI: 10.1186/s13046-019-1139-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of long non-coding RNA SBF2-AS1 enhances chemoresistance to temozolomide in glioblastoma

Abstract: Background: Acquired drug resistance is a constraining factor in clinical treatment of glioblastoma (GBM). However, the mechanisms of chemoresponsive tumors acquire therapeutic resistance remain poorly understood. Here, we aim to investigate whether temozolomide (TMZ) resistance of chemoresponsive GBM was enhanced by long noncoding RNA SBF2 antisense RNA 1 (lncRNA SBF2-AS1) enriched exosomes. Method: LncSBF2-AS1 level in TMZ-resistance or TMZ-sensitive GBM tissues and cells were analyzed by qRT-PCR and FISH as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
204
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 68 publications
2
204
0
1
Order By: Relevance
“…Exosomes released by cancer cells of the central nervous system (CNS) (e.g., brain tumor) or non-CNS (e.g., cancer that spreads from the periphery to the brain) can contribute to reduced cognition by modulating the cellular mechanism that perturbs brain function. Certain cancers (e.g., glioblastoma [78,93] and medulloblastoma [76,94]) arising from the CNS have been shown to express exosomes that could affect cellular integrity. For example, glioblastoma was shown to remodel the tumor microenvironment and lead to chemotherapy resistance (e.g., temozolomide) through the intracellular transfer of oncogenic long non-coding RNA SBF2-AS1 by exosomes [93].…”
Section: Cancer Exosomes and Cognitive Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes released by cancer cells of the central nervous system (CNS) (e.g., brain tumor) or non-CNS (e.g., cancer that spreads from the periphery to the brain) can contribute to reduced cognition by modulating the cellular mechanism that perturbs brain function. Certain cancers (e.g., glioblastoma [78,93] and medulloblastoma [76,94]) arising from the CNS have been shown to express exosomes that could affect cellular integrity. For example, glioblastoma was shown to remodel the tumor microenvironment and lead to chemotherapy resistance (e.g., temozolomide) through the intracellular transfer of oncogenic long non-coding RNA SBF2-AS1 by exosomes [93].…”
Section: Cancer Exosomes and Cognitive Impairmentmentioning
confidence: 99%
“…Certain cancers (e.g., glioblastoma [78,93] and medulloblastoma [76,94]) arising from the CNS have been shown to express exosomes that could affect cellular integrity. For example, glioblastoma was shown to remodel the tumor microenvironment and lead to chemotherapy resistance (e.g., temozolomide) through the intracellular transfer of oncogenic long non-coding RNA SBF2-AS1 by exosomes [93]. In addition to the ability to achieve chemoresistance, glioblastoma secretion of pro-permeability factor (e.g., Semaphorin3A) through exosomes has been associated with the loss of endothelial barrier integrity, resulting in debilitating cognitive deficits [78].…”
Section: Cancer Exosomes and Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…tested and identified miR‐151a loss pathway was key element of temozolomide‐resistant glioblastoma multiforme, and miR‐151a also provided a potential avenue for therapy‐refractory GBMs (Table ). Moreover, exosomal long‐noncoding RNA (lncRNA) SBF2‐AS1 (lncSBF2‐AS1), could also increase temozolomide tolerance to glioblastoma mainly via exerting reconstructive action to tumor microenvironment (Table ) . Qu et al .…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Moreover, exosomal long-noncoding RNA (lncRNA) SBF2-AS1 (lncSBF2-AS1), could also increase temozolomide tolerance to glioblastoma mainly via exerting reconstructive action to tumor microenvironment ( Table 1). 8 Qu et al 9 reported an identified lncARSR which increased the expression of AXL and c-MET, was transmitted to renal epithelial cell carcinoma cells, increased sunitinib tolerance (Table 1). Exosomal RNA also represents a novel strategy in enhancing chemosensitivity in cancer, not only for increased therapy tolerance.…”
Section: Therapy Resistancementioning
confidence: 99%